Leading for Innovation: The Interplay of Inclusive Leadership, Proactive Personality, and Creative Self-Efficacy in Hospitality Employees - Akhmad Darmawan; Uswatun Hasanah; Jovinda Percillia Marifatul Umairoh (Journal of Advanced Research in Social Sciences and Humanities, 2024)
Aim: The purpose of this study is to analyze an empirical research model that looks at how proactive personality traits, inclusive leadership, and creative self-efficacy affect creative work behavior in hospitality industry. Methodology: There were 162 respondents from hospitality employees from Indonesia which provided complete and useable response. Purposive sampling with non probabilty technique was the method used for sampling. Partial Least Squares (PLS) was then used to examine the gathered data. Findings: The analysis’s findings demonstrated that inclusive leadership, proactive personality traits and creative self efficacy revealed favorable significant impact on creative work practices in hospitality industry employees. Implications/Novel Contribution: The findings of this study carry significant implications for both management practices and human resource strategies within the hospitality sector, particularly in the context of Indonesia’s rapidly growing tourism industry. The positive influence of proactive personality traits, inclusive leadership, and creative self-efficacy on creative work behavior suggests that hotel organizations can enhance innovation and service quality by fostering these characteristics among employees. Managers should prioritize inclusive leadership practices that encourage open communication, employee participation, and recognition, as these create a supportive environment where creativity can thrive.